Stigma Rasisme Kulit Putih Terhadap Kulit Hitam sebagai Budak dalam Kemasan Sereal Kellogg’s - Lazuardian, Arga; Risqullah, Alif (Universitas Muhammadiyah Magelang, 2023)
Advertising serves as a means for prominent corporations to uphold their brand image. Racism can arise due to inadequate media utilization and a lack of advertising understanding, as Kellogg's Cereal exemplified in their 2017 advertisement